Purification, crystallization and preliminary X-ray diffraction analysis of the thiaminase type II from Staphylococcus aureus - Begum, Afshan (International Union of Crystallography, 2010)

(untitled)
Thiaminase type II (TenA) catalyzes the deamination of aminopyrimidines, including the cleavage of thiamine to 4-amino-5-hydroxymethyl-2-methylpyrimidine and 5-(2-hydroxyethyl)-4-methylthiazole in the metabolism of thiamine (vitamin B(1)), in Staphylococcus aureus (Sa). SaTenA was crystallized by the vapour-diffusion method and the resulting crystal diffracted to 2.6 Å resolution usng synchrotron radiation. The crystal is orthorhombic, belonging to space group P2(1)2(1)2(1) with unit-cell parameters a = 103.5, b = 104.1, c = 109.6 Å. With four molecules in the asymmetric unit, the Matthews coefficient is 2.85 Å(3) Da(−1). Initial attempts to solve the structure by molecular-replacement techniques were successful.